A dual‐color marker system for in vivo visualization of cell cycle progression in Arabidopsis. (29th September 2014) - Yin, Ke; Ueda, Minako; Takagi, Hitomi; Kajihara, Takehiro; Sugamata Aki, Shiori; Nobusawa, Takashi; Umeda‐Hara, Chikage; Umeda, Masaaki
Summary Visualization of the spatiotemporal pattern of cell division is crucial to understand how multicellular organisms develop and how they modify their growth in response to varying environmental conditions. The mitotic cell cycle consists of four phases: S (DNA replication), M (mitosis and cytokinesis), and the intervening G1 and G2 phases; however, only G2/M‐specific markers are currently available in plants, making it difficult to measure cell cycle duration and to analyze changes in cell cycle progression in living tissues. Here, we developed another cell cycle marker that labels S‐phase cells by manipulating Arabidopsis CDT1a, which functions in DNA replication origin licensing. Truncations of the CDT1a coding sequence revealed that its carboxy‐terminal region is responsible for proteasome‐mediated degradation at late G2 or in early mitosis. We therefore expressed this region as a red fluorescent protein fusion protein under the S‐specific promoter of a histone 3.1‐type gene, HISTONE THREE RELATED2 (HTR2), to generate an S/G2 marker. Combining this marker with the G2/M‐specific CYCB1‐GFP marker enabled us to visualize both S to G2 and G2 to M cell cycle stages, and thus yielded an essential tool for time‐lapse imaging of cell cycle progression. The resultant dual‐color marker system, Cell Cycle Tracking in Plant Cells (Cytrap), also allowed us to identify root cells in the last mitotic cell cycle before they entered the endocycle. Our results demonstrate that Cytrap is a powerful tool for in vivo monitoring of the plant cell cycle, and thus for deepening our understanding of cell cycle regulation in particular cell types during organ development.